Education Policy Analysis: Literature Review - Noorhayati, Siti Mahmudah; Hidayatullah (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The author will examine education policy including the scope of education policy analysis, various and models of education policy analysis and the limitations of education policy analysis. literature study method by conducting in-depth analysis of various articles that have been published in the last 10 years (2013-2023). Education is influenced by the results of a policy determined by the government, therefore choosing the right policy formulation model can produce good policies. There are several education policy models which are divided into three parts, namely (1) formulation model, (2) analysis model and (3) implementation model. The formulation model consists of institutional model, system model, mixed inquiry model, process model, elite theory model, rational model, incrementalist model, strategic model, deliberative model. Meanwhile, educational policy analysis models consist of prospective, retrospective and integrative models. The implementation model consists of top down and bottom up models. The current educational policy analysis model combines prospective, retrospective and integrative analysis.